THE TENTH GRADE STUDENTS’ PERCEPTION OF ANIMATION VIDEO AS MEDIA FOR LEARNING LISTENING AT SMK AL-HIKMAH JEPARA - Aldira, Ardiani Ivon; Rismiyanto, Rismiyanto; Madjdi, Ahmad Hilal (Prominent, 2024)
In this advanced information and communication era, technology can influence the educational practices of teachers and students. Watching Animation Video is one of the ways to develop listening skill and in this case, it refers to students’ perception of Animation Video as media for learning listening at SMK Al-Hikmah Jepara to gives them the authority to their listening skill. The objective of this research is aimed to know the students’ perception of Animation Video as media for learning listening at SMK Al-Hikmah Jepara. This kind of research is qualitative with a descriptive qualitative design. The participants of this research are 25 tenth grade students of AKL 1 at SMK Al-Hikmah Jepara. The instruments used in this study were questionnaires and interviews. The result of this study shows that the perception of the tenth grade AKL 1 students of SMK Al-Hikmah Jepara toward using Animation Video as media for learning listening, it can be concluded that most of the students agree to use Animation Video as media for learning listening. It means that the use of Animation Video as media for learning listening gives a potentially positive contribution to developing listening skills. Most students are enjoy and interested in using Animation Video as media for learning listening. Not only that the use of Animation Videos does not make students bored, but students become more active so they are more interested and of course, Animation Videos also help students in increasing vocabulary and developing listening skills. Therefore, hopefully, this research will help students improve their listening skills, especially through the use of Animation Video as listening learning media. Besides that, the researcher also suggests teachers be able to use Animation Videos as media for learning listening in class. Then the researcher suggests for the next researcher, in order to be able can explore more information about the students' perceptions of using Animation Video as media for learning listening in different methods.